Ciśnienie wewnątrzgałkowe u dzieci i młodzieży z krótkowzrocznością - Urban, Beata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To determine, whether intraocular pressure (IOP) is associated with myopia and axial length in children and adolescents. Material and methods: 129 patients in age from 9 to 18 years (mean 14.5 years), were examined. They underwent dynamic contour tonometry, cycloplegic autorefraction, and A-scan biometry. For analyses, refractive error was split into three groups: low myopia (spherical equivalent refraction – SE < -3.00 D), moderate myopia (SE from -3,00 D to -6,00 D), and high myopia (SE> -6.00 D). Results: There were no significant IOP differences between eyes with low (mean IOP = 15.15 mm Hg ± 2.73), moderate (15.3 mmHg ± 2.6) or high myopes (15.6 mmHg ± 2.33). IOP was not correlated with spherical equivalent refraction (p = 0.49) or axial length (Spearman correlation, r = 0.04). There were also no statistically significant differences in IOP between the less myopic and more myopic eyes of 11 patients with anisometropia > 3,00 D. Neither spherical equivalent (p = 0.49) nor axial length (p = 0.51) were significantly associated with IOP in anisometropic patients. Conclusions: IOP was not associated with refractive error and axial length in the eyes of myopic children and adolescents. Further observations are necessary, because myopia can be a risk factor in developing juvenile glaucoma.